2022
DOI: 10.7717/peerj.14200
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of prevalence and pattern of international consensus on ANA patterns among patients with hepatitis C virus infection

Abstract: Background A previous study reported a 30% prevalence of various autoantibodies among patients with hepatitis C virus (HCV) infection. The International Consensus on Anti-Nuclear Antibody (ANA) Patterns was recently introduced to classify ANA patterns based on immunoassay on HEp-2 cells. There is no previous report with this newly developed classification to evaluate patients with HCV infection. The study aims to study the prevalence and pattern of ANA patterns among HCV-infected patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…(Hep-20-10 cells, cutoff 1:320), 21 showing that female sex (p = 0.023), older age (p = 0.001), lower HCV RNA titer (p = 0.06), and more advanced brosis (p = 0.098) were associated with ANA positivity. An American retrospective study that included 1,556 patients with CHC who underwent autoantibody testing during 1997-2016 reported that 388 patients (21.8%) showed ANA positivity, and that the proportion of women was higher and the rate of SVR was lower among the autoantibody-positive patients, although ANA positivity had no impact on the clinical outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…(Hep-20-10 cells, cutoff 1:320), 21 showing that female sex (p = 0.023), older age (p = 0.001), lower HCV RNA titer (p = 0.06), and more advanced brosis (p = 0.098) were associated with ANA positivity. An American retrospective study that included 1,556 patients with CHC who underwent autoantibody testing during 1997-2016 reported that 388 patients (21.8%) showed ANA positivity, and that the proportion of women was higher and the rate of SVR was lower among the autoantibody-positive patients, although ANA positivity had no impact on the clinical outcomes.…”
Section: Discussionmentioning
confidence: 97%